The effect of magnaporthe oryzae on selected Malaysian rice varieties / Izuwan Mustafa Kamal - Mustafa Kamal, Izuwan (Faculty of Applied Sciences, 2016)
Rice or scientifically known as Oryza sativa Lis a staple crop of economic importance in many countries. However, rice had been infected with the most serious and widespread diseases which caused by the ascomycete fungus, Magnaporthe oryzae. Many study have been conducted towards the use of resistant cultivars as the methods to manage the blast disease. Present study was conducted to screen ten selected rice varities against fungus pathogen Magnaporthe oryzae namely MR 264, MR 211, MR 232, MR 220, MR 219, PS2, Kusam, Becok, Hita, and Pulut Wangi. PS2 and MR264 act as positive control due to their resistancy and susceptibility respectively. Result showed that after 14 days of inoculation, only MR 211 and MR 232 demonstrate resistance against the fungus infection. MR211 blast lesion area is 0.7 milimeter which is the lowest infected area compare with the other varieties. While MR 219 and MR 220 exhibit susceptible pattern against the blast infection. MR 219 recorded the highest blast lesion area measurement with 3.2 milimeter. Therefore it can be conclude that MR 211 and MR 232 could be a source of varieties to breed for development of resistant cultivar.